PURCHASING PRIAM: BILINGUAL WORDPLAY AT PLAUTUS BACCHIDES 976–7. (20th November 2014) - Cowan, Robert
Abstract : The conclusion of Chrysalus' famous canticum comparing the successful duping of his master Nicobulus to the sack of Troy has often been suspected by critics (Plaut. Bacch. 976–7):nunc Priamo nostro si est quis emptor, comptionalem senem uendam ego, uenalem quem habeo, extemplo ubi oppidum expugnauero. Now, if there's any buyer for our Priam, I'll sell as a job lot the old man, whom I have for sale as soon as I've stormed the city. The lines are condemned by Leo, Gaiser, and Jocelyn, but defended by Lefèvre and printed by Lindsay, Barsby, Questa (in his first and third editions, but not his second), and most recently De Melo. In addition to qualms about the inconsistency of casting Nicobulus as Priam here when he was Ilium little over thirty lines earlier – an inconsistency which can surely be attributed to the ebullience of Chrysalus rather than the incompetence of an interpolator – the main objection to these lines is their divergence from the mythological tradition about Priam's fate at the sack of Troy. As Jocelyn puts it, 'The threat senem uendam … would have been ludicrous to any audience acquainted with the heroic story.'